Digital Marketing dan Green Logistics Sebagai Strategi Pemasaran Berkelanjutan dalam Meningkatkan Kinerja Layanan Logistik UMKM Di Kawasan Industri Terpadu Batang - Devy Kusumaningrum; Karjono Karjono; Evyana Diah Kusumawati; Budi Purnomo (JURNAL TRANSMA, 2026)
This study aims to analyze the synergy between digital marketing and green logistics as a sustainable marketing strategy and its influence on the logistics service performance of Micro, Small, and Medium Enterprises (MSMEs) in the Batang Integrated Industrial Area (Batang IIA). Digital transformation and environmental sustainability pressures have driven the logistics industry to adopt adaptive and eco-friendly marketing strategies. This research employs a descriptive-qualitative approach with a case study design. A total of 12 informants from three stakeholder groups MSMEs, logistics companies, and industrial area managers were involved through semi-structured interviews, participatory observation, and documentation. The data were analyzed thematically. The findings reveal that MSMEs' adoption of digital marketing remains at an early stage, predominantly utilizing social media, while logistics companies have implemented it more comprehensively. The implementation of green logistics is still partial, primarily focused on operational efficiency through route optimization and fuel savings. The synergy between both strategies has been proven to improve delivery speed, cost efficiency, service reliability, and customer satisfaction. This study formulates an integrative model combining digital capabilities, green practices, integrated communication strategies, and ecosystem support as a sustainable marketing framework. Theoretically, this research enriches the literature on sustainable marketing and technology adoption in developing countries. Practically, it offers policy recommendations for industrial area managers, logistics companies, and MSMEs in developing a digital-based sustainable logistics ecosystem.